MAKING A CASE FOR SPORTS, SPORTS RIGHTS AND MEDIA RIGHTS IN NIGERIA: CONCEPTUAL PERSPECTIVES IN MEDIA RIGHTS AND INTELLECTUAL PROPERTY FRAMEWORK - Udeh, Kenneth Nwannebuike; Ebeze, Uche; Obioha, Benjamin Kelechi; Uwakwe, Onyeka (African Journal of Social and Behavioural Sciences, 2024)
Phenomenological evidence reveals that there is fervent passion for sports among Nigerians across diverse socio-economic, religious and political strata. However, this avid hunger has mainly been in favour of foreign football competitions organized by prominent football leagues in Europe and America, such as: the Spanish LaLiga, Bundesliga, Serie A, UEFA Champions League, Premier League, etc., and foreign football clubs: Chelsea, Manchester United, Arsenal FC, Manchester City, Liverpool, Tottenham Hotspur, etc. The concern is that the manifest degree of passion in sports, has, probably, not attracted genuine and commensurate interest in overall sports development in Nigeria. It appears that prolific investments in sports and sporting activities, for economic and commercial purposes, are rare; thus, current statistics indicates that the sports sector in Nigeria account for a meagre 0.005 percent of Nigeria’s Gross domestic product (GDP), much less than what is obtained in developed climes. Sports and sporting activities do not only serve the psychological, physiological and physiotherapeutic needs of mankind, for infotainment, relaxation, withdrawal from boredom and improvement in physical health; but also, investments in sports guarantee national development, through jobs creation and revenue generation; thereby, positively influencing the cultural, social and economic life of people across the globe. Anchored on Personality-based, Utilitarian and Natural Right theories of Intellectual Property, this paper examines the concept of sports, sports-media nexus and why sports, sports right and media right, should be enhanced in Nigeria, within the framework of Media Rights and Intellectual Property. We argued that sports production, organization and management are herculean tasks, involving money, time, energy and human intellect, and recommended, among others, that public-private partnership should be fashioned between government and popular private broadcast organizations, such that media or broadcast rights fees are subsidized, to aid public craving for and wide promotion of local sports. Similarly, to boost curiosity in local sports competitions, leagues and clubs, the government should concentrate more on improving sports technologies and evolving sports culture that could stand the test of time.